Esophageal Variceal Bleeding as the First Manifestation of COVID-19 Infection: A Case Report - Sotiropoulos, MD, MSc, Christos; Sakka, MD, Eftichia; Theocharis, MD, PhD, Georgios; Thomopoulos, MD, PhD, Konstantinos (International Journal of Innovative Research in Medical Science, 2022)
Liver cirrhosis is a defined liver disease with a wide range of clinical manifestations. Variceal bleeding is the main source of gastrointestinal hemorrhage among cirrhotic patients induced by several factors, such as alcohol consumption or infections. This is a report of a cirrhotic patient presenting with esophageal variceal bleeding in the context of COVID-19 infection. We report the case of a 53-year-old patient with liver cirrhosis and multifocal hepatocellular carcinoma presenting with upper gastrointestinal bleeding as the first manifestation of COVID-19 infection. Upon admission, the patient had no symptoms suggestive of a respiratory tract infection or any contact with positive SARS-CoV-2 individual and upper gastrointestinal endoscopy revealed variceal hemorrhage. After a few hours the patient manifested with fever, cough and dyspnea and a SARS-CoV-2 polymerase chain reaction test obtained was positive. The patient was initially treated with endoscopic band ligation and transferred in the COVID-19 infection clinic, where after a few days of hospitalization he passed away. The devastating pandemic of coronavirus disease 2019 had altered the pathophysiology and clinical presentation of several chronic diseases. This case report suggests that coronavirus disease as a potential triggering factor of variceal bleeding.